"I talked to a couple of friends that had it": Informal feminized health networks and contraceptive method choices. (October 2021) - Dalessandro, Cristen; Thorpe, Rachael; Sanders, Jessica
Abstract: Scholars recognize that social networks can influence a number of health behaviors, including women's contraceptive method choices. However, the gendered dynamics underlying the process of using non-medical information sources to make decisions about contraception has received less attention. Using 30 semi-structured interviews with women enrolled in a contraceptive initiative in the western United States, we explore how women use gendered understandings of medicine and feminized social networks to make decisions about contraceptives. Frequently categorizing their experiences in medical settings as unsatisfactory, women often turn to social support networks of other women—what we call "informal feminized health networks"—to gather information about the effects of contraceptives on women's bodies and to make decisions about which contraceptives are best. While informal feminized health networks are useful, women utilize them in light of unsatisfactory experiences in clinical settings. Working to uproot the paternalistic legacy of institutionalized medicine and improving provider-patient communication will enhance contraceptive access and help women reach their reproductive goals. Highlights: Women's informal health networks are an important resource regarding contraceptives. When unsatisfied with clinical encounters, social networks provide a safe alternative. Improved provider-patient communication may increase contraceptive access. Uprooting medicine's paternalistic institutional legacy should improve outcomes.